Candidate DNA repair susceptibility genes identified by exome sequencing in high-risk pancreatic cancer. Issue 2 (28th January 2016) - Smith, Alyssa L.; Alirezaie, Najmeh; Connor, Ashton; Chan-Seng-Yue, Michelle; Grant, Robert; Selander, Iris; Bascuñana, Claire; Borgida, Ayelet; Hall, Anita; Whelan, Thomas; Holter, Spring; McPherson, Treasa; et al.
Highlights: The genetic susceptibility of hereditary PC is highly heterogeneous. Rare germline protein-truncating DNA repair gene variants are common in PC. FAN1, NEK1 and RHNO1 are candidate PC susceptibility genes. Carriers of DNA repair gene mutations with early stage PC have worse survival. Abstract: The genetic basis underlying the majority of hereditary pancreatic adenocarcinoma (PC) is unknown. Since DNA repair genes are widely implicated in gastrointestinal malignancies, including PC, we hypothesized that there are novel DNA repair PC susceptibility genes. As germline DNA repair gene mutations may lead to PC subtypes with selective therapeutic responses, we also hypothesized that there is an overall survival (OS) difference in mutation carriers versus non-carriers. We therefore interrogated the germline exomes of 109 high-risk PC cases for rare protein-truncating variants (PTVs) in 513 putative DNA repair genes. We identified PTVs in 41 novel genes among 36 kindred. Additional genetic evidence for causality was obtained for 17 genes, with FAN1, NEK1 and RHNO1 emerging as the strongest candidates. An OS difference was observed for carriers versus non-carriers of PTVs with early stage (≤IIB) disease. This adverse survival trend in carriers with early stage disease was also observed in an independent series of 130 PC cases. We identified candidate DNA repair PC susceptibility genes and suggest that carriers of a germline PTV in a DNA repair gene with early stage disease have worse survival.